Trifluridine/tipiracil as a therapeutic option in real life setting of metastatic colorectal cancer: An efficacy and safety analysis - Sur, Daniel; Lungulescu, Cristina; Spînu, Ștefan; Gorzo, Alecsandra; Dumitrescu, Elena-Adriana; Gheonea, Dan Ionut; Lungulescu, Cristian-Virgil (Frontiers in Pharmacology, 2022)
Background: In the phase III RECOURSE trial, the orally administered combination trifluridine/tipiracil (FTD/TPI) demonstrated a survival benefit and an acceptable safety profile, earning approval as a third-line therapy in metastatic colorectal cancer (mCRC). This study aimed to assess the efficacy and safety of FTD/TPI in daily clinical practice in Romanian population. Methods: A single-center, retrospective, and observational study analyzed patients with mCRC that received chemotherapy with trifluridine/tipiracil between May 2019 and May 2022 at the Oncology Institute Prof. Dr. Ion Chiricuță in Cluj-Napoca, Romania. Study endpoints included safety, and median progression-free survival (PFS). Results: In this Romanian cohort (n=50) the most common treatment-emergent adverse event was haematological toxicity (76%): anemia (50%), leucopenia (38%), neutropenia (34%), and thrombocytopenia (30%), followed by fatigue (60%), and abdominal pain (18%). Overall, the median PFS was 3.85 months (95% CI: 3.1-4.6 months). PFS was significantly correlated with the number of FTD/TPI administrations and prior surgery. Conclusion: Our study corroborated the previously described safety profile for FTD/TPI in the third-line setting, and demonstrated relatively superior mPFS.